2021
DOI: 10.1007/s13300-021-01172-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of the FreeStyle Libre® System Versus Blood Glucose Self-Monitoring in Individuals with Type 2 Diabetes on Insulin Treatment in Sweden

Abstract: Introduction: Frequent glucose monitoring is essential to obtain glucose control. This is done by periodic self-monitoring of blood glucose (SMBG) using finger-prick testing, or by using continuous glucose monitoring devices, wherein a sensor records interstitial glucose data automatically. This study assessed the costeffectiveness of using the FreeStyle Libre Flash Continuous Glucose Monitoring System (FSL) compared to SMBG in individuals with type 2 diabetes (T2D) treated with insulin from a Swedish societal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…CGM has been shown to be clinically superior to SMBG at maintaining blood glucose levels within the euglycemic range [ 32 ]. Furthermore, a recent Swedish study showed long term improvements with CGM reducing HbA1c by 0.4% and it was cost-effective over the patient’s lifetime, both compared with SMBG [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…CGM has been shown to be clinically superior to SMBG at maintaining blood glucose levels within the euglycemic range [ 32 ]. Furthermore, a recent Swedish study showed long term improvements with CGM reducing HbA1c by 0.4% and it was cost-effective over the patient’s lifetime, both compared with SMBG [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The use of CGM in T2DM reduced acute diabetes complications in epidemiological studies [6][7][8][9][10] and had the potential to improve quality of life and diabetesrelated complications while reducing long-term healthcare costs. 11,12 The current clinical guidelines of the National Institute for Health and Care Excellence (NICE) recommend CGM to adults with type 2 diabetes on multiple daily insulin injections if one of the following applies: 1. They are otherwise advised to self-measure at least eight times a day 2.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of continuous glucose monitoring (CGM) in persons with type 2 diabetes (T2DM) have recently been documented in populations receiving basal insulin only, 1 basal‐bolus therapy 2,3 and even in patients not receiving insulin 4,5 . The use of CGM in T2DM reduced acute diabetes complications in epidemiological studies 6–10 and had the potential to improve quality of life and diabetes‐related complications while reducing long‐term healthcare costs 11,12 . The current clinical guidelines of the National Institute for Health and Care Excellence (NICE) recommend CGM to adults with type 2 diabetes on multiple daily insulin injections if one of the following applies: 1.…”
Section: Introductionmentioning
confidence: 99%
“…While previous work demonstrated the costeffectiveness of flash monitoring in people with T2D who are managed with intensive insulin [13][14][15], those analyses were based on a single RCT, which could be a limitation on the generalizability of the results. Therefore, our aim was to further assess the cost-effectiveness of flash glucose monitoring in view of recent clinical evidence, including both interventional and observational real-world studies, and explore the use of the device in T2D individuals from the UK health system perspective.…”
Section: Introductionmentioning
confidence: 99%